2022
DOI: 10.3390/jimaging8050136
|View full text |Cite
|
Sign up to set email alerts
|

Data Extraction of Circular-Shaped and Grid-like Chart Images

Abstract: Chart data extraction is a crucial research field in recovering information from chart images. With the recent rise in image processing and computer vision algorithms, researchers presented various approaches to tackle this problem. Nevertheless, most of them use different datasets, often not publicly available to the research community. Therefore, the main focus of this research was to create a chart data extraction algorithm for circular-shaped and grid-like chart types, which will accelerate research in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Otherwise, we solely encountered GI values that were represented as vertical bars from the 19 scholarly articles analysed in this research. Typically, bar graphs could be divided into basic, grouped, or stacked bars represented either vertically or horizontally as suggested by Bajic et al, and Mishra et al, in their respective research [16,49]. Based on this premise, we deduce that ImageJ could also be potentially utilized for data mining in linear plot graphs, box plots, 3-Dimensional (3D) bar graphs that are represented as single, grouped, or stacked graphs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Otherwise, we solely encountered GI values that were represented as vertical bars from the 19 scholarly articles analysed in this research. Typically, bar graphs could be divided into basic, grouped, or stacked bars represented either vertically or horizontally as suggested by Bajic et al, and Mishra et al, in their respective research [16,49]. Based on this premise, we deduce that ImageJ could also be potentially utilized for data mining in linear plot graphs, box plots, 3-Dimensional (3D) bar graphs that are represented as single, grouped, or stacked graphs.…”
Section: Discussionmentioning
confidence: 85%
“…In general, according to Bajic et al, data represented as figures could be either automatically or interactively extracted [16]. These could be carried out via photo editing programs, image processing programs or custom coded algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The tabular data from the tables of a paper could be handled using data analysis libraries including Pandas; 89 however, it is important to standardize the tabular data because the formats of the table are much different across papers and journals. For gures, numerous vision techniques are rapidly developing which are applicable to a graph 90 and microscopy images, 91,92 which were proven to be very effective to extract the data from the gures in papers. Lastly, we observed that the NER performance is lower for catalyst name entities than for other entities, probably because researchers describe catalyst names in various forms in different papers.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al devised a method to generate textual descriptions for graphs that summarize information about the value relationships [32]. Researchers have also investigated automated data extraction from simple numerical charts, such as bar charts and pie charts [10,33,34]. For curve graphs, Figureseer can analyze the content on the graph while extracting the numerical value, including the association information of the legend entries [35].…”
Section: Related Researchmentioning
confidence: 99%